2020
DOI: 10.7759/cureus.11346
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Infodemic: A Quantitative Analysis Through Facebook

Abstract: Background Social media is a crucial part of our daily life. Facebook, being the biggest social media platform, plays a significant role in the spread of information influencing the global response to the COVID-19 pandemic. Health care agencies like the World Health Organization (WHO) and Centers for Disease Control and Prevention (CDC) use social media as a platform to impart information regarding COVID-19; simultaneously, there is a spread of misinformation on social media, masking the credible sources of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 17 publications
2
31
0
1
Order By: Relevance
“…Over 37% of the most viewed YouTube videos with the Korean term "Coronavirus" and its variations were found to contain misleading information ( Andreu-Sánchez and Martín-Pascual, 2020 ). High percentages of misinformation were also found when the search was conducted in English or on other platforms (e.g., Facebook and Twitter) ( Li et al., 2020 ; Ahmed et al., 2020 ; Ahmed et al., 2020 ). Similar findings were also reported by a considerable amount of studies ( Ahmed et al., 2020 ; Pulido et al., 2020 ; Moon and Lee, 2020 ; Bârgăoanu and Durach, 2020 ; Khatri et al., 2020 ; Ataç et al., 2020 ; D'Souza et al., 2020 ; Dutta et al., 2020 ; Kocyigit et al., 2020 ; Yüce et al., 2020 ; Yuksel and Cakmak, 2020 ; Kawchuk et al., 2020 ; Raja and Shaheed, 2020 ; Almomani and Al-Qur'an, 2020 ; Cuan-Baltazar et al., 2020 ; Szmuda et al., 2020 ; Moscadelli et al., 2020 ; Obiała et al., 2021 ; Mackey et al., 2020 ; Safarnejad et al., 2020 ; Tagliabue et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over 37% of the most viewed YouTube videos with the Korean term "Coronavirus" and its variations were found to contain misleading information ( Andreu-Sánchez and Martín-Pascual, 2020 ). High percentages of misinformation were also found when the search was conducted in English or on other platforms (e.g., Facebook and Twitter) ( Li et al., 2020 ; Ahmed et al., 2020 ; Ahmed et al., 2020 ). Similar findings were also reported by a considerable amount of studies ( Ahmed et al., 2020 ; Pulido et al., 2020 ; Moon and Lee, 2020 ; Bârgăoanu and Durach, 2020 ; Khatri et al., 2020 ; Ataç et al., 2020 ; D'Souza et al., 2020 ; Dutta et al., 2020 ; Kocyigit et al., 2020 ; Yüce et al., 2020 ; Yuksel and Cakmak, 2020 ; Kawchuk et al., 2020 ; Raja and Shaheed, 2020 ; Almomani and Al-Qur'an, 2020 ; Cuan-Baltazar et al., 2020 ; Szmuda et al., 2020 ; Moscadelli et al., 2020 ; Obiała et al., 2021 ; Mackey et al., 2020 ; Safarnejad et al., 2020 ; Tagliabue et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Facebook and other social media platforms have the capacity to disseminate accurate information, create influential public health messages and facilitate the rollout of vaccines. 30–32 The Centers for Disease Control and Prevention (CDC) and state departments of health are using Facebook for public health messaging in social networks, albeit with varying levels of success. A study of over 2500 CDC and health department Facebook posts found 7% concerned vaccines and immunization, and most states with lower childhood and influenza vaccination coverage are not utilizing Facebook to promote immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Flashy news, media, and editorializing in both academic journals and the popular press may be prominent during the pandemic. [21][22][23][24] It is unknown whether non-peer-reviewed news stories and in-house editorials in major journals help safeguard against the "infodemic" or sometimes contribute to make things worse. Excluding journalists and editors of prestigious journals, the key countries of the authors with the highest composite citation indicator tended to be similar to the countries of the most prolific authors.…”
Section: Discussionmentioning
confidence: 99%